1983
DOI: 10.1017/s0021859600035565
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Terpal on the yield and yield components of oil-seed rape (Brassica napus L.)

Abstract: The objective of this study was to examine the effect of the chemical growth regulator Terpal (a mixture of mepiquat chloride and ethephon or 2 chloroethyl phosphonic acid) on the pattern of branching, plant height and yield components of winter oil-seed rape (cv. Jet Neuf). Mepiquat chloride (a quaternary ammonium compound with similar antigibberellin properties to cycocel) was developed as a morphoregulator for cotton where it has been shown to reduce plant height, shorten internodes and increase boll retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies on the use of PGRs in oilseed rape have been reported (Chapman, 1982;Daniels & Scarisbrick, 1986;Smith, 1987). These have tended to concentrate on the physiological effects induced by PGRs leading to effects on yield and its components (Chapman, Scarisbrick & Daniels, 1983;Scarisbrick, Addo-Quaye, Daniels & Mahamud, 1985; Addo-Quaye, . In wheat and barley, although the possibilities of inhibitors of gibberellin biosynthesis such as paclobutrazol (PP333) and chlormequat chloride causing changes in crop physiology beneficial to yield are well known (Humphries, 1968;Froggatt, Thomas & Batch, 1982;Waddington & Cartwright, 1986), recommendations for commercial use emphasise the benefits from the prevention of lodging (Anon., 19894.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the use of PGRs in oilseed rape have been reported (Chapman, 1982;Daniels & Scarisbrick, 1986;Smith, 1987). These have tended to concentrate on the physiological effects induced by PGRs leading to effects on yield and its components (Chapman, Scarisbrick & Daniels, 1983;Scarisbrick, Addo-Quaye, Daniels & Mahamud, 1985; Addo-Quaye, . In wheat and barley, although the possibilities of inhibitors of gibberellin biosynthesis such as paclobutrazol (PP333) and chlormequat chloride causing changes in crop physiology beneficial to yield are well known (Humphries, 1968;Froggatt, Thomas & Batch, 1982;Waddington & Cartwright, 1986), recommendations for commercial use emphasise the benefits from the prevention of lodging (Anon., 19894.…”
Section: Introductionmentioning
confidence: 99%